Key users of Polish digital libraries - Górny, Miros aw; Mazurek, Jolanta (Electronic library, 2012)
Purpose - The article concerns efforts to identify the key users of Polish digital libraries.Design methodology approach - The research was based on a questionnaire containing 19 questions, on subjects which included ways of using the library, reasons for using it, and which types of publications were most often used. Use was also made of statistical data collected on the library's server. An attempt was made to characterize the dominant groups of digital library users, taking a user's interests as the main determinant. The analysis focused on age, sex, level of education, and size of town where users reside. An attempt was also made to determine approximately the total number of users.Findings - Approximately 60 per cent of users are amateur historians with an interest in the history of their place of residence or genealogists interested in the history of their family. The remaining 40 per cent consist mainly of academic researchers and students. The number of regular readers - those who use the library at least several times per year - is approximately 30,000. There will probably be a significant rise in the number of users in the amateur historians and genealogists category. One of the factors that may affect the number of users is the expansion of information technology infrastructure in rural areas. This will undoubtedly cause a significant rise in the number of internet users, although the number of digital library users will probably increase only marginally as a result of this. A second factor is the spreading of internet skills in the over-70 age group. In a few years' time that group will be more numerous. The group that affords the greatest prospects for expansion is students. Firstly this is a group that numbers two million people in Poland, and secondly they require universal access to textbooks. A cause for concern is the minimal interest in digital libraries shown by teachers and school pupils.Research limitations implications - This is the first stage of research into the function performed by digital libraries in Polish society.Originality value - This is the first study carried out in Poland to answer the question of who uses digital libraries, to what extent, and why.